2009
DOI: 10.1111/j.1751-553x.2009.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of acute leukemia

Abstract: Summary Acute leukemia is the commonest childhood cancer and a major cause of morbidity from hematologic malignancies in adults. Acute lymphoblastic leukemia (ALL) is commonest in children, and acute myeloid leukemia (AML) is more frequent in adults. Apart from childhood ALL, the prognosis of acute leukemia is suboptimal, with many patients experiencing relapse, which carries a poor prognosis, or toxicities from nonspecific therapies. Recent years have witnessed great interest in the application of high‐resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 117 publications
0
11
0
Order By: Relevance
“…[43][44][45] In summary, this study revealed an essential role for the Mef2c/d proteins in regulating transition through the first checkpoint in early development by integrating the MAPK signals of the pre-BCR to a downstream transcriptional network, thereby controlling proliferation and orchestrating the progression through the next phase of B-cell development. In view of growing recognition that disruption of pre-BCR controls can lead to leukemia, 75,76 this work provides insight into the mechanism by which MEF2C and MEF2D disruption [23][24][25] contributes to acute lymphoblastic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45] In summary, this study revealed an essential role for the Mef2c/d proteins in regulating transition through the first checkpoint in early development by integrating the MAPK signals of the pre-BCR to a downstream transcriptional network, thereby controlling proliferation and orchestrating the progression through the next phase of B-cell development. In view of growing recognition that disruption of pre-BCR controls can lead to leukemia, 75,76 this work provides insight into the mechanism by which MEF2C and MEF2D disruption [23][24][25] contributes to acute lymphoblastic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate small copy number changes in a genomewide manner array-based comparative genome hybridization (aCGH) can be applied (SolinasToldo et al, 1997;Albertson and Pinkel, 2003;Fiegler et al, 2003). In childhood acute lymphoblastic leukemia, this approach has led to the identification of alterations in genes like PAX5 or IKAROS, previously not implicated in the pathogenesis of the disease (Mullighan, 2009). One major advantage of applying aCGH to the analysis of MDS, a disease characterized by enhanced levels of apoptosis and often by a hypocellular marrow (Clark and Lampert, 1990;Niemeyer et al, 1992;Kerbauy and Deeg, 2007), is that no dividing cells are needed.…”
Section: Introductionmentioning
confidence: 99%
“…This technique can be used to introduce or correct disease phenotypes such as β‐thalassemia or Alzheimer disease in induced pluripotent stem cell (iPSC) …”
Section: A Future Perspective: Crispr Therapy?mentioning
confidence: 99%